POTENSI TANAH MENGEMBANG DI KABUPATEN PURWAKARTA, JAWA BARAT - -, Zufialdi Zakaria; -, Edi Tri Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
Based on Geological Map of Pamanukan Sheet (scale 1:100.00) and Karawang Sheet (1:100.000), at northern ward of Purwakarta Regency, there are some rocks formation, e.g. Jatiluhur Formation, Subang Formation, and some Aluvials. Swelling potential analysis is based on Seed Method (Seed, et al.,1962, from Hunt, 2007). Soil samples at Aluvial terrain shows swelling characteristics very high (usually at clay of Subang Formation), its activity value is 1.31, predicted monmorilonitic (Bowles, 1989). Soil sample at clay terrain of Subang Formation shows low swelling potential (its not characteristic of Subang Formation), activity value is 0.21 (is predicted Illitic based on Bowles, 1989), and soil sample at clay terrain of Jatiluhur Formation, shows medium swelling potential characteristic with activity value is 0.52.